তাজউদ্দীন আহমদের সমাজ ও রাষ্ট্রভাবনা : নির্বাচিত বক্তৃতা - আহমদ, তাজউদ্দীন, ১৯২৫-১৯৭৫
Selected speeches of Tājauddina Āhamada, 1925-1975, politician and first Prime Minister of Bangladesh, on contemporary socio-political issues of Bangladesh.